I got this nice question from my friend.

If

\[A = \displaystyle \sum_{n=1}^{\infty} \frac{1}{n(2^n - 1)}\]

and

\[B_{k} = \frac{2}{1} \times \frac{4}{3} \times \frac{8}{7} \times \ldots \times \frac{2^k}{2^k - 1}\]

then prove that

\[\lim_{k \to \infty} B_{k} = e^A\]

No vote yet

5 votes

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet \(B = \displaystyle\lim_{k \to \infty}B_k\) \(= \displaystyle\prod_{m = 1}^{\infty} \dfrac{2^m}{2^m-1}\).

Then, \(\ln B = \displaystyle\sum_{m = 1}^{\infty}\ln\left(\dfrac{2^m}{2^m-1}\right)\) \(= \displaystyle\sum_{m = 1}^{\infty}-\ln\left(\dfrac{2^m-1}{2^m}\right)\) \(= \displaystyle\sum_{m = 1}^{\infty}-\ln\left(1 - 2^{-m}\right)\)

\(= \displaystyle\sum_{m = 1}^{\infty}\sum_{n = 1}^{\infty}\dfrac{(2^{-m})^n}{n}\) \(= \displaystyle\sum_{n = 1}^{\infty}\sum_{m = 1}^{\infty}\dfrac{(2^{-n})^m}{n}\) \(= \displaystyle\sum_{n = 1}^{\infty} \dfrac{1}{n} \dfrac{2^{-n}}{1 - 2^{-n}}\) \(= \displaystyle\sum_{n = 1}^{\infty} \dfrac{1}{n(2^n-1)} = A\).

Since \(\ln B = A\), we have \(B = e^A\), as desired.

Because all terms are positive, every sum above is absolutely convergent, so all the steps are justified.

Log in to reply

Can you please explain how you introduced the second summation? Thank you!

Log in to reply

I used the Taylor series \(-\ln(1-x) = \displaystyle\sum_{n = 1}^{\infty}\dfrac{x^n}{n}\) which is absolutely convergent for \(|x| < 1\).

Log in to reply

Log in to reply

Nice, thanks Jimmy!

Log in to reply